Factors associated with parenting practices among preschoolers' parents in Ampang and Serdang, Selangor, 2016 - Ramli, N. A. A. N.; Mohd Jamil, N. F.; Kadir @ Shahar, Hayati; Baharom, Anisah (International Journal of Children, Women, Elderly and Disable People, 2017)
Parenting practices is an important factor that determines child's behaviour. In the past 40 years, research proves that child’s development are affected by parenting. Hence, it is also important to know that there are factors that are associated with the parenting practice because that factors can determine whether the parenting being used is good or bad. To determine the factors (parents’ attitude, parental knowledge) associated with parenting practices among preschoolers' parents in Ampang and Serdang, Selangor. This was a cross-sectional study. Self-administered questionnaires were used to collect data from 252 preschoolers’ parents from 14 Tabika KEMAS in Ampang and Serdang, Selangor. The data collected were analysed by using SPSS version 21.0. Parental knowledge (source) and parents’ attitude (overprotective, interest in knowledge) were the most common factors affecting parenting practices of preschoolers' parents from 14 Tabika KEMAS in Ampang and Serdang, Selangor. Overall, parents play an important role in developing skills of good parenting practices to be applied on their children later on.